The effect of elevated serum estradiol levels on the day of human chorionic gonadotropin injection on pregnancy outcomes in an assisted reproduction program - (:unkn) unknown (WILEY-BLACKWELL PUBLISHING, INC, 2009)
Background: Women who have a high estradiol level on the day of human chorionic gonadotropin injection are considered to have their in vitro fertilisation treatments compromised. How this really affects the pregnancy rates needs to be questioned. Aim: To determine if elevated serum estradiol levels on the day of human chorionic gonadotropin injection have a deleterious effect on clinical and ongoing pregnancy rates in an assisted reproduction program. Methods: A retrospective analysis was done of women with estradiol levels higher than 10 000 pmol/L and women with estradiol levels between 8000-10 000 pmol/L on the day of ovulation trigger undergoing in vitro fertilisation treatment at the Fertility Unit of the Royal Prince Alfred Hospital, University of Sydney, Australia. Pregnancy rates were compared for those having fresh embryo transfers and those having frozen thawed embryo transfers in subsequent cycles. Results: There was no difference between the groups in terms of clinical and ongoing pregnancy rates. Conclusion: Frozen thawed embryos obtained from controlled ovarian hyperstimulation cycles resulted in similar clinical and ongoing pregnancy rates as those obtained in previous fresh embryo transfer cycles.
Keywords: ART; embryo transfer; estradiol; high responder; pregnancy; CONTROLLED OVARIAN HYPERSTIMULATION; FERTILIZATION-EMBRYO TRANSFER; INVITRO FERTILIZATION; ELECTIVE CRYOPRESERVATION; PREIMPLANTATION PERIOD; OVULATION INDUCTION; UTERINE RECEPTIVITY; TRANSFER CYCLES; HIGH RESPONDERS; IMPLANTATION